Checkmate office politics - Dalal, Bhavna (New Delhi Sage, 2020)
"No one likes office politics. These words usually invoke negative imagery, such as blaming, backstabbing, favoritism and talking behind one's back. Like it or loathe it, professional success is not merely dependent on merit; being able to read people and their motives is what keeps one ahead"--
Keywords: Office politics; Organizational behavior